2021
DOI: 10.1371/journal.pone.0258543
|View full text |Cite
|
Sign up to set email alerts
|

Expression profile of tumour suppressor protein p53 and its regulator MDM2 in a cohort of breast cancer patients in a Tertiary Hospital in Ghana

Abstract: Background Inactivation or mutation of the tumour suppressor gene p53 or its regulator mouse double minute 2 (MDM2) is the commonest event in breast cancer. These altered genes usually express abnormally high levels of their proteins in many carcinomas. The phenotypic expression of p53 and MDM2 in breast cancer cases in our setting is not known. This study investigated the expression of the tumour suppressor protein p53 and its regulator MDM2, using immunohistochemistry in a Ghana breast cancer cohort. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…NDC80 is a protein Coding gene that encodes the NDC80 kinetochore complex components (NUF2). It may be involved in preneoplastic processes, as it is detected in benign breast tumors [ 74 ]. Xu et al [ 75 ] had reported that NUF2 is overexpressed in breast cancer and significantly connected to multiple pathological features and prognosis of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…NDC80 is a protein Coding gene that encodes the NDC80 kinetochore complex components (NUF2). It may be involved in preneoplastic processes, as it is detected in benign breast tumors [ 74 ]. Xu et al [ 75 ] had reported that NUF2 is overexpressed in breast cancer and significantly connected to multiple pathological features and prognosis of breast cancer.…”
Section: Discussionmentioning
confidence: 99%